Patients perception related to pulmonary tuberculosis and adherence medication - Manurung Nixson; Harahap R. Hamdani; Siregar Fazidah A.; Andayani Lita Sri (E3S Web of Conferences)
Pulmonary tuberculosis is a global health problem that could impact on productivity and quality of life. Prevalance of pulmonary tuberculosis was 929 meanwhile only 48.87% with taking medicine. The adherence of pulmonarytuberculosis patients in taking medication is the key for successfull tuberculosis treatment. The aims of this study to explore the perception of patients related to pulmonary tuberculosis and adherence medication. This is a qualitative study with a phenomenological approach. Data collection using in-depth interviews and then analyzed by content analysis. The informants in this study consisted of 10 tuberculosis patients. The results of this study found three themes, namely (1) Prolonged disease, (2) Disease transmission, (3) Adherence medication. It was concluded that a better understading about tuberculosis disease and adherence treatment could contribute to the succesfull of treatment. It was suggested that patient could be aware and encourage to take adherence medication.